Changes in Mortality on Weekend versus Weekday Admissions for Acute Coronary Syndrome in the United States over the past Decade - Khoshchehreh, Mahdi (Int J Cardiol, 2016)
BACKGROUND: We assessed in-hospital mortality and utilization of invasive cardiac procedures following Acute Coronary Syndrome (ACS) admissions on the weekend versus weekdays over the past decade in the United States. METHODS: We used data from the Nationwide Inpatient Survey (2001–2011) to examine differences in all-cause in-hospital mortality between patients with a principal diagnosis of ACS admitted on a weekend versus a weekday. Adjusted and hierarchical logistic regression model analysis was then used to identify if weekend admission was associated with a decreased utilization of procedural interventions and increased subsequent complications as well. RESULTS: 13,988,772 ACS admissions were identified. Adjusted mortality was higher for weekend admissions for Non-ST-Elevation Acute Coronary Syndromes [OR: 1.15, 95% CI, 1.14–1.16] and only somewhat higher for ST-Elevation Myocardial Infarction [OR: 1.03; 95% CI, 1.01–1.04]. Additionally, patients were significantly less likely to receive coronary revascularization intervention/therapy on their first day of admission [OR: 0.97, 95% CI: 0.96–0.98 and OR: 0.75, 95% CI: 0.75–0.75 for STEMI and NSTE-ACS respectively]. For ACS patients admitted during the weekend who underwent procedural interventions, in-hospital mortality and complications were higher as compared to patients undergoing the same procedures on weekdays. CONCLUSION: For ACS patients, weekend admission is associated with higher mortality and lower utilization of invasive cardiac procedures, and those who did undergo these interventions had higher rates of mortality and complications than their weekday counterparts. This data leads to the possible conclusion that access to diagnostic/interventional procedures may be contingent upon the day of admission, which may impact mortality.